Bart’s Syndrome Associated Corpus Callosum Agenesis and Choanal Atresia - SAEED*, Muhammad; HAQ, Anwar ul; QADIR, Khaqan (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Saeed M, Haq A, Qadir Kh.Bart’s Syndrome Associated Corpus Callosum Agenesis and Choanal Atresia. Iran J Child Neurol. 2014 Autumn;8(4): 76-79. Abstract Objective Bart’s syndrome is defined as congenital localized absence of skin, and associated with epidermolysis bullosa. A newborn with Bart’s syndrome is reported because it is a very rare condition, especially when associated with corpus callosum agenesis and concomitant choanal atresia. Clinically it is characterized by raw beefy areas of denuded skin mainly on hands and feet. We report a rare case of a term female newborn born to non-consanguineous parents who presented with congenital absence of skin in, face, trunk and extremities. To the best of our knowledge, this is the first report presenting a case of Bart’s syndrome associated with corpus callosum agenesis. References Bart BJ, Garlin RJ, Anderson VE, Lynch FW. Congenital localized absence of skin and associated abnormalities resembling epidermolysis bullosa. A new syndrome. Arch Dermatol 1966; 93: 296-304. Bart BJ. Epidermolysis bullosa and congenital localized absence of skin. Arch Dermatol 1970; 101: 78-81. Skoven I, Drzewiecki KT. Congenital localized skin defect and epidermolysis bullosa hereditaria letalis. Acta Derm Venereol 1979; 59: 533-537. Wojnarowska FT, Eady RA, Wells RS. Dystrophic epidermolysis bullosa presenting with congenital localized absence of skin: report of four cases. Br J Dermatol 1983; 108: 477-483. Kanzler MH, Smoller B, Woodley DT. Congenital localized absence of the skin as a manifestation of epidermolysis bullosa. Arch Dermatol 1992; 128:1087-90. Maman E, Maor E, Kachko L, Carmi R. Epidermolysis bullosa, pyloric atresia, aplasia cutis congenita: histopathological delineation of an autosomal recessive disease. Am J Med Genet 1998; 78: 127-133. McCarthy MA, Clarke T, Powell FC. Epidermolysis bullosa and aplasia cutis. Int J Derm 1991; 30: 481-484. Puvabanditsin S, Garrow E, Daeun K. Junctional epidermolysis bullosa associated with congenital localized absence of skin. J AM Acad Dermatol 2001; 44: 330-335. Joensen HD. Epidermolysis bullosa dystrophica dominans in two families in the Faroe Islands. Acta Derm Venereol 1973; 53: 53-60. Skoven I, Drzewiecki KT. Congenital localized skin defect and epidermolysis bullosa hereditaria letalis. Acta Derm Venereol 1979; 59: 533-7. Birnbaum RY, Landau D, Elbedour K, Ofir R, Birk OS, Carmi R. Deletion of the first pair of fibronectin type III repeats of the integrin beta-4 gene is associated with epidermolysis bullosa, pyloric atresia and aplasia cutis congenita in the original Carmi syndrome patients. Am J Med Genet 2008; 146A: 1063-1066. Rajpal A, Mishra R, Hajirnis K, Shah M, Nagpur N. Bart’s syndrome. Indian J Dermatol 2008; 53: 88-90. Zelickson B, Matsumara K, Kist D, Epstein EH, Jr, Bart BJ: Bart’s syndrome. Ultrastructure and genetic linkage. Arch Dermatol 1995;131:663–668. Christinano AM, Bart BJ, Epstein EH Jr, Uitto J: Genetic basis of Bart’s syndrome: A glycine substitution mutation in the type VII collagen gene. Invest Dermatol 1996;106: 1340–1342.